Disruption of Sinonasal Epithelial Nrf2 Enhances Susceptibility to Rhinosinusitis in a Mouse Model. (6th July 2020) - Ramanathan, Murugappan; Tharakan, Anuj; Sidhaye, Venkataramana K.; Lane, Andrew P.; Biswal, Shyam; London, Nyall R.
Abstract : Objectives/Hypothesis: Oxidative stress has been postulated to play an important role in chronic rhinosinusitis. Nrf2 is a transcription factor that is involved in the regulation of multiple antioxidant genes, and its function has been previously shown to be important in sinonasal inflammation. Although the sinonasal implications of whole body Nrf2 −/− has been reported, the function of sinonasal epithelial expression of Nrf2 has not been studied. The primary aim of this study was to generate a mouse model that is genetically deficient in epithelial‐specific Nrf2 and to understand its role in regulating sinonasal inflammation. Study Design: Basic science. Methods: An epithelial‐specific Nrf2 knockout mouse was generated by crossing Krt5‐cre(K5) with Nrf2 flox/flox . A papain‐induced model of rhinosinusitis was performed in the resulting K5 Nrf2 −/− mouse. Immunohistochemistry was performed to quantify goblet cell hyperplasia. Mucosal cellular infiltrates were quantified using flow cytometry, and tissue cytokines were measured using an enzyme‐linked immunosorbent assay. Lastly, the cellular source of type 2 cytokines was determined using intracellular cytokine staining. Results: Papain‐sensitized mice lacking epithelial‐specific Nrf2 demonstrate increased goblet cell hyperplasia, significant tissue eosinophilia, and statistically significant increase in mucosal IL‐13 when compared to Nrf2 wild‐type mice. Lastly, mucosal T cells were identified as the cellular source of IL‐13. Conclusions: We demonstrate enhanced severity of eosinophilic sinonasal inflammation from disruption of the epithelial‐specific Nrf2 pathway. The responsiveness of Nrf2‐directed antioxidant pathways may act as a major determinant of susceptibility to eosinophilic inflammation and may have potential as a therapeutic target for chronic rhinosinusitis. Level of Evidence: NA Laryngoscope, 131:713–719, 2021